2018
DOI: 10.1037/lat0000089
|View full text |Cite
|
Sign up to set email alerts
|

Latino/a freshman struggles: Effects of locus of control and social support on intragroup marginalization and distress.

Abstract: The transition to college can be difficult for many students; however, Latina/o students can face unique cultural stressors, impacting psychological health. Intragroup marginalization, or feeling marginalized by members within one's cultural community, is one such stressor that can impact Latina/o students' college experiences. Despite the challenges many Latina/o students face, Latina/os also demonstrate resilience and the ability to succeed. This study expands existing research on intragroup marginalization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 114 publications
3
15
1
Order By: Relevance
“…A total of 30 studies were found that adhered to the inclusion criteria set for the systematic review. Of these, 16 focused on social support and psychological outcomes (Abu-Kaf et al, 2018;Adamczyk, 2015;Bíró, Veres-Balajti, & Kósa, 2016;Ceglarek & Ward, 2016;Frison & Eggermont, 2015;Kim, Kim, & Lee, 2016;Llamas, Morgan Consoli, Hendricks, & Nguyen, 2018;Marhamah & Hamzah, 2016;Ng, Wang, & Chan, 2017;Roohafza et al, 2016;Tang & Dai, 2018;Vungkhanching, Tonsing, & Tonsing, 2016;Wang, Sun, & Wang, 2016;Wongtongkam, 2019;Yıldırım, Karaca, Cangur, Acıkgoz, & Akkus, 2017;You, Lim, & Kim, 2017); 3 focused on social support and academic achievement (Bai et al, al., 2018; Rodríguez et al, 2017); 4 focused on social support and technology use (Deechuay, Koul, Maneewan & Lerdpornkulrat, 2016;Gökçearslan, Uluyol & Şahin, 2018;Shah, Siddiqui & Ansari, 2016;; 4 focused on sources of social support (Bhochhibhoya et al, 2017;Chuah & Singh, 2016;Lee & Goldstein, 2016;Rios & Eaton, 2016); and 3 focused exclusively on gender differences in social support (Lin, 2016;Zamani-Alavijeh, Raeesi Dehkordi, & Shahry, 2017;Zhang, Zhapng, Zhang, Zhang, & Feng, 2018). All studies except one were quantitative.…”
Section: Research Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 30 studies were found that adhered to the inclusion criteria set for the systematic review. Of these, 16 focused on social support and psychological outcomes (Abu-Kaf et al, 2018;Adamczyk, 2015;Bíró, Veres-Balajti, & Kósa, 2016;Ceglarek & Ward, 2016;Frison & Eggermont, 2015;Kim, Kim, & Lee, 2016;Llamas, Morgan Consoli, Hendricks, & Nguyen, 2018;Marhamah & Hamzah, 2016;Ng, Wang, & Chan, 2017;Roohafza et al, 2016;Tang & Dai, 2018;Vungkhanching, Tonsing, & Tonsing, 2016;Wang, Sun, & Wang, 2016;Wongtongkam, 2019;Yıldırım, Karaca, Cangur, Acıkgoz, & Akkus, 2017;You, Lim, & Kim, 2017); 3 focused on social support and academic achievement (Bai et al, al., 2018; Rodríguez et al, 2017); 4 focused on social support and technology use (Deechuay, Koul, Maneewan & Lerdpornkulrat, 2016;Gökçearslan, Uluyol & Şahin, 2018;Shah, Siddiqui & Ansari, 2016;; 4 focused on sources of social support (Bhochhibhoya et al, 2017;Chuah & Singh, 2016;Lee & Goldstein, 2016;Rios & Eaton, 2016); and 3 focused exclusively on gender differences in social support (Lin, 2016;Zamani-Alavijeh, Raeesi Dehkordi, & Shahry, 2017;Zhang, Zhapng, Zhang, Zhang, & Feng, 2018). All studies except one were quantitative.…”
Section: Research Resultsmentioning
confidence: 99%
“…Overall, the impact of social support on all variables related to psychological outcomes was found to be positive, with findings showing negative correlation between social support and depression (Abu-Kaf et al, 2018;Roohafza et al, 2016;Tang & Dai, 2018;Vungkhanching et al, 2016), anxiety (Roohafza et al, 2016;Vungkhanching et al, 2016), stress (Marhamah & Hamzah, 2016;Vungkhanching et al, 2016), neuroticism (Roohafza et al, 2016), negative effects (Wang et al, 2016) and positive correlation between social support and sense of coherence (Bíró et al, 2016), relationship status (Adamczyk, 2015), positive effects (Wang et al, 2016), workplace engagement (Kim et al, 2016), emotional regulation (You et al, 2017), fewer mental health symptoms (Ceglarek & Ward, 2016) and cultural adaptation (Ng et al, 2017). Social support emerged as a predictor of emotional distress (Llamas et al, 2018;Wongtongkam, 2019), stress (Yıldırım et al, 2017), marginalization (Llamas et al, 2018) and cultural adaptation (Ng et al, 2017). These findings were reported from diverse range of regions and cultures, representing male undergraduates from countries such as Australia (Wongtongkam, 2019), Belgium (Frison & Eggermont, 2015), China (Tang & Dai, 2018;Wang et al, 2016), Hong Kong (Ng et al, 2017), Hungary (Bíró et al, 2016), Indonesia (Marhamah & Hamzah, 2016), Iran (Roohafza et al, 2016), Israel (Abu-Kaf et al, 2018, Korea (Kim et al, 2016;...…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When counseling LGBTQ college students, counselors may find it beneficial to explore how these students' connections can serve as tools of resiliency. Social support has been found to mediate effects of marginalization on psychological distress (Farrell & Langrehr, ; Llamas, Morgan Consoli, Hendricks, & Nguyen, ; Llamas & Ramos‐Sánchez, ). The college setting can provide unique opportunities of support (e.g., offices of diversity and inclusion) for LGBTQ clients to help strengthen relational ties, maximize power derived from these supportive relationships in the face of adversity, and develop a stronger connection to the campus environment.…”
Section: Rct In Action With Lgbtq College Studentsmentioning
confidence: 99%